Does the World Cup get the economic ball rolling? Evidence from a synthetic control approach - Jorge H. N. Viana; Antonio Vinicius Barbosa; Breno Sampaio (EconomiA, 2018)
In this paper we analyze the impact of hosting the FIFA Soccer World Cup on GDP per capita in a worldwide sample of countries using a transparent statistical methodology for data-driven case studies - the synthetic control method. Using country level annual-data covering all events occurring in the period between 1978 (Argentina) and 2006 (Germany), we show that the estimated average treatment effect was either zero or negative for all but one of the countries analyzed. Our results, therefore, support the general claim that World Cups are not statistically associated to development and economic growth.
Keywords: O4; O5; C50; 330; Economic growth; Synthetic control method; World Cup